Bond valence sum analysis of pyrochlore oxides including the novel dielectric Te6+ pyrochlores: ABiMTeO7-y (A = Cd, Ca; M = Cr, Ga, Sc, In, Fe). (December 2022) - Converse, Elizabeth Sobalvarro; King, Gabriella; Li, Jun; Subramanian, M.A.
Abstract: Bond valence sum analysis is a powerful tool used in evaluating and validating crystal structures; especially when those structures are complex in nature. The pyrochlore structure type is versatile in not only the unique bonding that it exhibits, but also in the properties that results from the structure. This paper aims to center the discussion of evaluating the pyrochlore structure using the bond valence sum method. In this study, novel quaternary pyrochlores with a general stoichiometry of A Bi M TeO7 ( A  = Cd, Ca; M  = Cr, Ga, Sc, In, Fe) were synthesized and characterized for their structural, magnetic, and dielectric properties. Two representative compounds within this series of pyrochlores, BiCaFeTeO7 and BiCdFeTeO7, were structurally characterized utilizing a combination of high-resolution synchrotron X-ray diffraction and neutron diffraction revealing oxygen deficient pyrochlore systems which were off from the expected stoichiometry with respect to the M site. The A site of both pyrochlores were found to be moved off-center from the expected 16 d site to the 96 h displaced position at a magnitude of 0.25 Å and 0.22 Å for the Bi/Ca and Bi/Cd systems, respectively. These structures were evaluated using the bond valence sum method and compared with trends in the literature. The properties are also reported for the Bi/Ca system for the first time, showing relatively high dielectric constants with a low dielectric loss which are primarily independent of frequency and temperature. The magnetic measurements for the Bi/Ca system for the magnetic substitutions reveal a paramagnet and antiferromagnetic properties for the Fe and Cr analogs, respectively. The novel BiCa M TeO7 quaternary pyrochlore system shows great promise as an emerging dielectric material. Graphical abstract: (a) A Bond Valence Sum (BVS) cross-sectional map for a (b) segmented portion of the BiCdFeTeO7 structure. Image 1